The Cortical Basal ganglia Functional Scale (CBFS): Development and preliminary validation. (October 2020) - Lang, Anthony E.; Stebbins, Glenn T.; Wang, Ping; Jabbari, Edwin; Lamb, Ruth; Morris, Huw; Boxer, Adam L.; ,; Boxer (PI), A.; Boeve, B.; Dickerson, B.; Grossman, M.; et al.
Abstract: Objective: To develop a patient/care-giver reported scale capable of easily and reliably assessing functional disability in 4 repeat tauopathies (4RTs). Background: 4R tauopathies including progressive supranuclear palsy, corticobasal degeneration and a subset of frontotemporal dementias manifest a range of overlapping clinical phenotypes. No available rating scale is capable of evaluating the functional impact of these complex disorders. Methods: A multi-staged modified Delphi process was used to propose, evaluate and rank potential scale items providing content validity ratios. Staged cognitive pretesting involving input from examiners, patients and caregivers was followed by validation testing in patients participating in the 4R Tauopathy Neuroimaging Initiative or the PROgressive Supranuclear Palsy CorTico-Basal Syndrome MSA Longitudinal Study. Clinimetric properties were examined using classical test theory and item response methods, assessing data quality, reliability, construct validity, convergent validity and known-group validity. Results: The resultant Cortical Basal ganglia Functional Scale (CBFS) included questions on Motor Experiences in Daily Living (14 items) and Non-Motor Experiences of Daily Living (17 items). Reliability was acceptable for internal consistency, test-retest stability, item discrimination, item-scaling thresholds and item-fit. Examination of construct validity revealed a parsimonious two-factor solution, and concurrent validity demonstrated significant correlations between the CBFS and other measures of disease severity and functional impairment. The CBFS significantly discriminated between all diagnostic groups and controls (all AUCs>90). The CBFS scores demonstrated sensitivity to change over a 12 month follow-up in patients with probable 4RTs. Conclusions: The CBFS is a patient/care-giver reported outcome measure with excellent clinimetric properties that captures disability correlated with motor, cognitive and psychiatric impairments. Highlights: There is considerable clinical and pathogenic overlap between the 4R tauopathies (PSP, CBD). There is no available rating scale capable of evaluating the functional impact of the complex disorders that constitute the 4R tauopathies. Disease modifying trials directed at common pathogenic factors will require scales that evaluate the complex clinical phenotypes. Patient/caregiver reported outcomes are increasing emphasized in drug development. The CBFS is a newly developed scale using patient/caregiver reported information that was designed to address these unmet needs.